Tranexamic Acid-Induced Acute Renal Cortical Necrosis in Post-Endoscopic Papillectomy Bleeding - Doo Hyun Ko; Tae Hyung Kim; Jong Wook Kim; Ja Joong Gu; Baek Hyun Yoon; Ji Hong Oh; Seung Goun Hong (Korean Society of Gastrointestinal Endoscopy, 2017)
Acute renal failure can be the result of acute renal cortical necrosis (RCN), which commonly occurs from complications occurring during pregnancy. RCN is rarely caused by medications, although tranexamic acid, which is used in patients with acute bleeding for its antifibrinolytic effects, reportedly causes acute RCN in rare cases. An 82-year-old woman experienced gastrointestinal bleeding after endoscopic papillectomy of an ampullary adenoma. The bleeding was controlled with tranexamic acid administration; however, 4 days later, her urine volume decreased and she developed pulmonary edema and dyspnea. Serum creatinine levels increased from 0.8 to 3.9 mg/dL and dialysis was performed. Abdominal pelvic computed tomography with contrast enhancement revealed bilateral RCN with no renal cortex enhancement. Renal dysfunction and oliguria persisted and hemodialysis was continued. Clinicians must be aware that acute RCN can occur after tranexamic acid administration to control bleeding.